Habiletes Sociales Acquises Au Sein Des Familles Et Resilience Au Passage A L’acte Delictueux Chez Des Jeunes Vivant Dans Des Quartiers Defavorises A Abobo. (Abidjan) - Traore Massandjé; Crizoa Hermann; N’goran N’faissoh Franck Stéphane (European Scientific Journal, ESJ, 2018)
This study aims to explain the link between the social skills acquired within families and the resilience to the criminal act in young people living in disadvantaged neighborhoods in Abobo. The research was carried out in Abobo commune and involved 74 participants from different social categories. The collection of information relating to the object of study was based on questionnaire, interview and observation. The information collected was analyzed from a quantitative and qualitative point of view. The results of the study indicate that youth who are resilient to delinquency in the community are of all ages and both sexes. The study shows that the resilience to the criminal act in certain young people living in the precarious neighborhoods of the Abobo commune is explained by the ability to ask for help, self-control, development of a sense of autonomy and a projection into the future.